Swagata: A New High-Yielding Variety ofElephant Foot Yam - Sarkar, Mangaldeep; Jadav, N K; Chaudhari, B N (Indian Horticulture, 2024)
Elephant foot yam [Amorphophallus paeoniifolius (Dennst.), syn. A. campanulatus (Roxb.) BL. ex Dence] is herbaceous, and one of the tropical perennial vegetables that originated in Southeast Asia. It is C3 in nature, vegetatively propagated and commercially cultivated for its underground modified stem or corm which has long been used as a local staple food in many countries. The corms are usually consumed after frying, boiling or baking and are rich in vitamin A phosphorus and calcium. The petioles and leaves are also eaten in India by local tribes as they too contain a high concentration of vitamin A. The corms are reported to have blood purifying properties and are used in medicines for the treatment of asthma, piles, dysentery and other abdominal disorders. Navsari Agricultural University started a crop improvement programme on elephant foot yam by collecting germplasm from local as well as from different parts of India and evaluated them to discover elite genotypes for the farmers of tribal regions and all over Gujarat. Following the breeding method of clonal selection, one elite genotype was developed and after the recommendation of 51st State Seed Sub-Committee, Gandhinagar, Gujarat it was released by the name of Swagata. Farmers of Gujarat prefer this variety specifically for higher productivity, disease resistance, excellent corm flesh colour and palatability.